Electrochemical Cross-Coupling Reactions between Arylboronic Esters and Aryllithiums Using NaBr as a Halogen Mediator - Mitsudo, Koichi; Shigemori, Keisuke; Shibata, Taro; Mandai, Hiroki; Sato, Eisuke; Suga, Seiji (Synthesis, 2023)
An electrochemical cross-coupling reaction between arylboronic esters and aryllithiums was developed. The presence of Br– in the electrolyte was found to be essential for the reaction. NaBr was chosen as the electrolyte for its inexpensiveness and abundance, and also acted as a halogen mediator. The reaction proceeded under mild conditions to afford biaryls.
Keywords: electro-oxidation; anodic oxidation; cross-coupling; transition-metal-free; biaryl